2021
DOI: 10.3791/63094-v
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Pericarditis in Aachener Minipigs As a Model for Atrial Myopathy and Atrial Fibrillation

Abstract: We describe a sterile pericarditis model in minipigs for the study of atrial myopathy and atrial fibrillation (AF). We present surgical and anesthetic techniques, strategies for vascular access, and a protocol to study the inducibility of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent study showed a model of sterile pericarditis-induced atrial myopathy in Aachen minipigs, suggesting a model of structural remodeling in AF. 12 The study demonstrated that atrial fibrosis resulting from the inflammation of the pericardium and myocardium preceded the induction of AF. In comparison with our study, the progressive increases in pacing thresholds over time are consistent.…”
Section: Swine Versus Canine Sterile Pericarditis Model For Studying ...mentioning
confidence: 95%
See 2 more Smart Citations
“…A recent study showed a model of sterile pericarditis-induced atrial myopathy in Aachen minipigs, suggesting a model of structural remodeling in AF. 12 The study demonstrated that atrial fibrosis resulting from the inflammation of the pericardium and myocardium preceded the induction of AF. In comparison with our study, the progressive increases in pacing thresholds over time are consistent.…”
Section: Swine Versus Canine Sterile Pericarditis Model For Studying ...mentioning
confidence: 95%
“…Recently, the swine has been increasingly used for cardiac research because it has similar physical and electrophysiological properties to humans, and is socially more accepted 10,11 . Although a recent study reported a model of sterile pericarditis‐induced atrial myopathy in Aachen minipigs, the study failed to induce POAF during postoperative period (within 5 days) after open heart surgery 12 . The purpose of this study is to validate the feasibility of the swine sterile pericarditis model as an experimental counterpart to study POAF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation